PERCEPTION OF UNISMA STUDENTS ON AUDIO-VISUAL TEACHING MATERIALS IN QIRO’AH LEARNING: A STUDY BASED ON MAYER’S MULTIMEDIA LEARNING THEORY - Jannah, Rauzatul; Ibrahim, Faisal Mahmoud Adam; Syuhadak, Syuhadak (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Purpose: This study examines the perceptions of students at the Islamic University of Malang regarding the use of audio-visual teaching material in Qiro’ah Learning, with particular attention to learning motivation. Method: Employing a qualitative phenomenological approach, the study is grounded in Richard E. Mayer’s Multimedia Learning Theory, which highlights the integration of visual and auditory elements to enhance learning effectiveness. Data were collected through in-depth interviews, participatory observation, and documentation involving ten students from the Arabic Language Education program enrolled in a Qiro’ah course. Result: The findings reveal that audio-visual teaching materials have a positive influence on students’ learning motivation, cognitive engagement, and reading comprehension. Conclusion: Student reported improved understanding of textual meaning, greater learning interest, and increased enthusiasm during the learning process, indicating that multimedia-based instruction supports more meaningful and engaging Qiro’ah learning experiences.